Identification of a myotropic AAV by massively parallel in vivo evaluation of barcoded capsid variants - Weinmann, Jonas; Weis, Sabrina; Sippel, Josefine; Tulalamba, Warut; Remes, Anca; El Andari, Jihad; Herrmann, Anne-Kathrin; Pham, Quang H.; Borowski, Christopher; Hille, Susanne; Schönberger, Tanja; Frey, Norbert; et al. (Nature Communications, 2020)
Adeno-associated virus (AAV) forms the basis for several commercial gene therapy products and for countless gene transfer vectors derived from natural or synthetic viral isolates that are under intense preclinical evaluation. Here, we report a versatile pipeline that enables the direct side-by-side comparison of pre-selected AAV capsids in high-throughput and in the same animal, by combining DNA/RNA barcoding with multiplexed next-generation sequencing. For validation, we create three independent libraries comprising 183 different AAV variants including widely used benchmarks and screened them in all major tissues in adult mice. Thereby, we discover a peptide-displaying AAV9 mutant called AAVMYO that exhibits superior efficiency and specificity in the musculature including skeletal muscle, heart and diaphragm following peripheral delivery, and that holds great potential for muscle gene therapy. Our comprehensive methodology is compatible with any capsids, targets and species, and will thus facilitate and accelerate the stratification of optimal AAV vectors for human gene therapy.
Gesehen am 29.04.2021